Modernizing, Expanding, and Measuring the Impact of FDA on Food Safety Initiatives (2025)
With this current proposal, IICA seeks to build on the successes of the past two Cooperative Agreements and implement high-impact interventions that directly reduce risks associated with importing food into the United States. It will continue enhancing capacities to facilitate the implementation, adoption, and compliance of specific FSMA regulations across Latin America and the Caribbean, leveraging its prior efforts.